THU0269 SERUM IL-6 AND CIRCULATING IMMUNE COMPLEXES AS BIOMARKERS OF DISEASE ACTIVITY IN MULTI-ETHNIC ASIAN SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2019) - Samuel Lee, Shang Ming; Howe, Hwee Siew; Thong, Bernard Yu-Hor; Kong, Kok Ooi; Chng, Hiok Hee; Lian, Tsui Yee; Chia, LI-Ann Faith; Lau, Tang Ching; Law, Weng Giap; Koh, Ee Tzun; Bernard Leung, Pui Lam
Abstract : Background: IL-6 plays an important role in B cell hyperactivity and immunopathology of systemic lupus erythematosus (SLE), and may have a direct role in mediating tissue damage [1]. Elevated levels of serum circulating immune complexes (CICs) have been described in SLE but the relationship with disease activity in our multi-ethnic Asian patients remains unclear. Objectives: To determine the correlation between disease activity and the levels of CICs, serum and urine IL-6 in a Singapore cohort of multi-ethnic Asian SLE patients. Methods: Serum levels of CICs, IL-6 and urine IL-6 were measured in 88 SLE patients using CIC-C1q and high sensitivity IL-6 ELISAs. All patients fulfilled the 1997 revised American College of Rheumatology (ACR) classification criteria. Clinical and laboratory manifestations, therapy, disease activity and damage at the time of sample collection was collated. Disease activity was scored with the SLE Activity Measure-revised (SLAM-R) and damage with the ACR/Systemic Lupus International Collaborating Clinic SLE damage index (SDI). The correlation between disease activity score and CICs, serum and urine IL-6 were assessed using Spearman's correlation. Receiver operator characteristic (ROC) curve analysis was performed to assess the performance of the individual biomarkers in discriminating SLE disease activity. Results: The cohort of 88 patients were predominantly female (n = 78, 89.6%), with a mean age of 40 years±13.1. The majority were of Chinese ethnicity (n = 73, 83%), 13% were Malay (n = 11) and 4 individuals were of other races. The mean disease duration was 98.4 months ± 86.4. The mean scores of SLAM-R and SDI were 2.9 ± 2.2 and 0.9 ± 0.9 respectively. SLE disease manifestations at the time of sample collection included mucocutaneous involvement (5.7%) and active urine sediment (28.7%). 77% had hypocomplementaemia and 70.1% had elevated titres of anti-dsDNA antibody. The majority were on corticosteroids (75.9%) and hydroxycholoroquine (65.5%). Immunosuppressive drugs included azathioprine in 37.9%, mycophenolate in 6.9%, intravenous pulse cyclophosphamide in 6.9% and cyclosporin in 1 patient. There was significant positive correlation between SLAM-R and serum CICs (R = 0.4121, p < 0.01), serum IL-6 (R = 0.4227, p < 0.01) and urine IL-6 (R = 0.3142, p = 0.01). Based on the area under the curve(AUC), CICs and urine IL-6 were better in discriminating active SLE (AUC 0.8002, p < 0.01 and AUC 0.7397, p < 0.01 respectively) compared to serum IL-6 (AUC 0.5554, p = 0.1718). Conclusion: Our study observed significant correlation between levels of serum circulating immune complexes, serum and urine IL-6 with SLE disease activity in our multi-ethnic Asian patient cohort. ROC curve analysis suggests that serum CICs and urine IL-6 may serve as sensitive biomarkers to identify SLE patients at risk of flares. Reference: [1] Tackey E, et al. Rationale for interleukin-6 blockade in systemic lupus erythematosus. Lupus. 2004;13(5):339-43. Disclosure of Interests: None declared